Comparative impact of small-sided games and high-intensity interval training on physical performance in youth soccer players (2023)
ABSTRACT: Small-sided games (SSGs) serve as a valuable tool for aerobic training for both professional and amateur teams. Nevertheless, some studies suggest that, under specific conditions, small SSGs may not replicate the highintensity efforts (20–25 km/h) and repeat sprints (>25 km/h) demanded by full games when compared with larger small-side game formats or match play. Conversely, high-intensity interval training (HIIT) has been shown to enhance maximal oxygen uptake, the lactic threshold, intermittent high-intensity effort capabilities, and rapid recovery between intense efforts. This study aimed to evaluate the effects of SSGs in comparison to HIIT on maximal oxygen uptake (VO2MAX), repeat sprint ability (RSA), and agility in youth soccer players. A randomized parallel-group study involving 12 players per group was conducted. The experimental group underwent a nine-week SSGs-based intervention, ranging from two vs. two to six vs. six formats, with a training duration between 20 and 40 min, while the control group engaged in HIIT for the same duration and frequency. The testing battery (baseline and postintervention) occurred over three different days with assessments at 8:00 a.m., both at the club’s training ground (Course Navette, Sprint Repeated Test, and Illinois Test) and in the laboratory (ergospirometry) with an environmental temperature of 24°C and relative humidity of 60%. The study commenced in the middle of the competitive season. Statistical analyses revealed no significant differences in maximal oxygen uptake between the SSGs-based training group and the control group (p = 0.44). However, the experimental group exhibited a 6% improvement in performance, while the control group showed a 12% improvement, with a moderate effect size (ES = 0.4). Additionally, the experimental group demonstrated statistically significant improvements in all RSA variables: best time (p = 0.02; 95% confidence interval (CI95%): −0.18; −0.01; ES = 1.1), average time in all sprints (p = 0.005; CI95%: −0.33; −0.06; ES = 1.4), total time in all sprints (p = 0.003; CI95%: −2.17; −0.52; ES = 1.4), and the percentage of decrease tended towards significance (p = 0.07; CI95%: −3.07; 0.15; ES = 0.8) compared with the control group. Agility showed no significant differences between the two groups (p = 0.45). Overall, no statistically significant differences were found in maximal oxygen uptake and agility between youth soccer players practicing SSGs and those engaged in HIIT after nine weeks. Notably, a significant enhancement in repeat sprint ability was observed in the SSGs group compared to the HIIT group. Consequently, during the in-season, amateur team coaches should favor SSGs training instead of interval exercises to optimize training